2015
DOI: 10.1158/1535-7163.mct-14-0531
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Characterization of RSM-932A, a Novel Anticancer Drug Targeting the Human Choline Kinase Alpha, an Enzyme Involved in Increased Lipid Metabolism of Cancer Cells

Abstract: Choline kinase a (CHKA; here designated as ChoKa) is the first enzyme in the CDP-choline pathway, implicated in phospholipids metabolism. It is overexpressed in several human tumors such as breast, lung, bladder, colorectal, prostate, ovary, and liver. The overexpression of ChoKa has oncogenic potential and synergizes with other known oncogenes. It has been proposed as a novel cancer drug target with a distinct mechanism of action. We have generated a set of ChoKa inhibitors with potent in vitro antiproliferat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 47 publications
0
58
1
Order By: Relevance
“…Consistently, pharmacological inhibitors of CHKA has also displayed antiproliferative, proapoptotic and antitumoral effects against multiple tumor-derived cancer cells as well as tumor xenografts [18, 23, 32, 4346]. Indeed, one CHKA inhibitor, designated as TCD-717 or RSM-932A, has recently completed Phase I clinical trials for the treatment of advanced solid tumors (ClinicalTrial.gov Identifier: NCT01215864) [27]. Thus, together our findings with what has been reported so far, inhibition of CHKA may have a broad spectrum application as an attractive novel anticancer strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, pharmacological inhibitors of CHKA has also displayed antiproliferative, proapoptotic and antitumoral effects against multiple tumor-derived cancer cells as well as tumor xenografts [18, 23, 32, 4346]. Indeed, one CHKA inhibitor, designated as TCD-717 or RSM-932A, has recently completed Phase I clinical trials for the treatment of advanced solid tumors (ClinicalTrial.gov Identifier: NCT01215864) [27]. Thus, together our findings with what has been reported so far, inhibition of CHKA may have a broad spectrum application as an attractive novel anticancer strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its regular function (19), CHKA was reported to be important in cancer carcinogenesis and development (8,20). Granata et al reported that CHKA could act as a potential druggable target for ovarian cancer by regulating cell aggressiveness and drug sensitivity (21).…”
Section: Discussionmentioning
confidence: 99%
“…Lacal and colleagues have tested several groups of compounds that inhibit ChKα activity, some of which displayed significant levels of antiproliferative activity and led to a reduction of tumor growth (65–67). One of these inhibitors, TCD-717 (68), is currently being tested in a phase I clinical trial (). Bhujwalla and colleagues have developed siRNA and shRNA strategies (Figure 3) (69, 70), and siRNA-based nanoparticles against ChKα (71) for anticancer therapy.…”
Section: Choline Kinase αmentioning
confidence: 99%